Pemanfaatan trichoderma sebagai agen hayati yang efektif meningkatkan keuntungan petani bawang merah di Kabupaten Majene - Dewi, Suryani; Suyono, Suyono; Fitri, Fitri (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2024)
This community service aims to educate shallot farmers in Majene Regency about the benefits of Trichoderma sp.. as a biological agent in controlling plant diseases, as well as the economic benefits of farmers in using it. The activity was carried out in August 2023 in Pamboborang Village, Banggae District using the methods of counseling, discussion, and demonstration. The results showed that this activity increased farmers' knowledge and awareness about the use of Trichoderma sp.. which can reduce the use of chemical pesticides, reduce production costs, and increase shallot yields. Simulation of costs and economic benefits in the use of Trichoderma in shallot farming shows the potential for increasing farmers' income by up to 69%. The follow-up recommendation of this activity is the continuous assistance from relevant stakeholders in the development of environmentally friendly shallot farming to achieve sustainable and profitable agriculture.